GUI Elements and Windows Form Formalization Parameters and Events Method to Automate the Process of Additive Cyber-Design CPPS Development - Nevliudov, I.; Yevsieiev, V.; Lyashenko, V.; Ahmad, M. Ayaz (Research India Publications, 2021)
This article presents a method for formalizing parameters, GUI elements and Windows Forms events for the development of Cyber-Physical Production Systems based on object-oriented programming languages cybernetic component HMI additive cyber design. The proposed method will allow to automate the HMI CPPS development process by setting a unique "Lingustic Variable" which refers to "Container Solution" containing a piece of program code that must be implemented in accordance with the requirements of the technical specifications. The developed method allows to reduce the time for creating an additive cyber design, which will increase the efficiency of managing new and old CPPS modernization development.
Keywords: Industry 4.0; Additive Cyber Design